University radios and networks: management models and user profiles - Marta-Lazo, Carmen; Segura-Anaya, Ana (Historia y Comunicación Social, 2014)
The university radio is experiencing a golden age due to lower costs of production and worldwide distribution that allows the Network Increasingly broadcasters who opt for the broadcast via the Internet, while supplying the social networks as adjuncts to promote their programs and dissemination of information. This article aims to determine, through a survey of their directors, the use made of the educational radio networks and what their management models.
Keywords: University radios; social networks; management models; uses